Artykuł oryginalnySexual dysfunctions and marital adjustment in veterans with PTSD - Ahmadi, Khodabakhsh; Fathi-Ashtiani, Ali; Zareir, Ali; Arabnia, Alireza; Amiri, Mandana (Archives of Medical Science, 2006)
Introduction: Considering that we have in Iran a lot of veterans who suffer from post-traumatic stress disorder (PTSD), this research was performed to identify sexual dysfunction among a group of veterans who suffer from PTSD. Material and methods: In this descriptive-correlation research we selected and studied 110 cases. Data gathering tools were sexual dysfunctions, PTSD checklist according to DSM-IV and Enrich marital satisfaction scale. Under study sexual dysfunctions in this research include: decrease of libido, decrease of arousal, premature ejaculation, aversion to intercourse, erectile dysfunction, ejaculation delay, masturbation, painful ejaculation, or without problem. Results: The results show 89.1% of veterans with PTSD, at least one with sexual dysfunction and only 10.9% with no problems. Also the results show that most dysfunction includes: decrease of libido (68.2%), decrease of arousal (61.8%) and premature ejaculation (41.8%).Other results show that 45.5%, i.e. nearly half of the PTSD subjects, were dissatisfied with their marriage and sexual relationship and the dissatisfaction level of 11% was very high. Discussion: Veterans afflicted with PTSD face marital maladjustment, which predisposes them to sexual disorders. Therefore, marriage counselling and prevention programmes should focus on reducing marital dissatisfaction. If marital maladjustment decreases, sexual problems and disorders will improve.